2011
DOI: 10.1124/dmd.111.041467
|View full text |Cite
|
Sign up to set email alerts
|

UDP-Glucuronosyltransferase (UGT) 1A9-Overexpressing HeLa Cells Is an Appropriate Tool to Delineate the Kinetic Interplay between Breast Cancer Resistance Protein (BRCP) and UGT and to Rapidly Identify the Glucuronide Substrates of BCRP

Abstract: ABSTRACT:The interplay between phase II enzymes and efflux transporters leads to extensive metabolism and low bioavailability for flavonoids. To investigate the simplest interplay between one UDPglucuronosyltransferase isoform and one efflux transporter in flavonoid disposition, engineered HeLa cells stably overexpressing UGT1A9 were developed, characterized, and further applied to In conclusion, the engineered HeLa cells overexpressing UGT1A9 is an appropriate model to study the kinetic interplay between UGT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 34 publications
4
48
0
Order By: Relevance
“…We also demonstrated that cellular excretion of CG was contributed by multiple efflux transporters (including BCRP, MRP1, MRP3, and MRP4) using a combined approach of chemical inhibition and shRNA-mediated silencing. Our findings were consistent with the study of Jiang et al (2012) in which BCRP was involved in excretion of flavonoid glucuronides in HeLa cells. However, Jiang et al (2012) showed that contributions of MRP family proteins (e.g., MRP2/ MRP3) to glucuronide excretion were negligible.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We also demonstrated that cellular excretion of CG was contributed by multiple efflux transporters (including BCRP, MRP1, MRP3, and MRP4) using a combined approach of chemical inhibition and shRNA-mediated silencing. Our findings were consistent with the study of Jiang et al (2012) in which BCRP was involved in excretion of flavonoid glucuronides in HeLa cells. However, Jiang et al (2012) showed that contributions of MRP family proteins (e.g., MRP2/ MRP3) to glucuronide excretion were negligible.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings were consistent with the study of Jiang et al (2012) in which BCRP was involved in excretion of flavonoid glucuronides in HeLa cells. However, Jiang et al (2012) showed that contributions of MRP family proteins (e.g., MRP2/ MRP3) to glucuronide excretion were negligible. In our study, we provided strong evidence that MRP family proteins contributed significantly to excretion of CG.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The data points in figures are observed glucuronidation rates, and the curves are plotted using the fitted kinetic parameters (Table 2). MRP2 and BCRP are important transporters for the efflux of glucuronides (Jiang et al, 2012). We found that the amount of calycosin-39-glucuronide in the perfusate samples significantly decreased in the presence of MK571 and ko143 (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…A better understanding of transporter-enzyme interplay contributes to improved predictions of in vivo drug disposition and drug-drug interactions (Benet et al, 2003;Lam et al, 2006). In addition to P-glycoprotein/cytochrome p450 3A, the interplay is also applicable to the efflux transporters (i.e., breast cancer resistance protein and MRPs) and phase II enzymes (Jiang et al, 2012;Zhang et al, 2015). The dependence of phase II metabolism on efflux transporters is underpinned by the fact that the hydrophilic phase II metabolites (lacking in passive transport ability) require the efflux transporters for cellular excretion (Wu, 2012).…”
Section: Introductionmentioning
confidence: 99%